Economic growth in South East Asia and its consequences for the environment - Axel Michaelowa (Intereconomics, 1996)
The debate on environmental policy generally focuses on the industrialized countries. It is often neglected that rapid economic growth in the newly industrializing countries is certain to lead to the rise of environmental issues on a large scale. Especially Eastern and South East Asia will witness major environmental degradation in the next few decades unless appropriate environmental policy measures accompany further economic growth.
Keywords: 330